PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L) MENGGUNAKAN BERBAGAI SISTEM TANAM PADA VARIETAS YANG BERBEDA - Putra, Heriyansah Dwi; Muhanniah, Muhanniah; Hasanuddin, Fenny (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
Rice is the most important food crop in Indonesia. Indonesian people use rice as a daily staple, because rice contains a source of sugar and energy. The aim of the research is to determine the planting systems, varieties and interactions between planting systems and varieties that provide the highest growth and production in rice plants. This research uses a 2 factor factorial design, the first factor is the planting system which consists of 3 treatments: 20 x 20 cm tile planting system, 25 x 25 cm tile planting system, and 2 row legowo planting system: 1, the second factor is Variety (V) which consists of 2 treatments, namely the Ciherang Variety and the Mekongga Variety. The observation parameters are plant height, number of tillers, number of productive tillers, number of perennial seeds, weight of permalai seeds, weight of 1000 grains, and weight of grain per unit. The research results showed that the Jajar Legowo 2:1 planting system gave the highest average number of tillers, namely 24.8 stems, and the highest number of productive saplings with an average of 18.9 stems. The Ciherang variety has a higher plant height and number of perennial seeds than the Mekongga variety